Synthesis of ε-Caprolactone by Oxidation of Cyclohexanone with Monoperoxysuccinic Acid - 陈建 赵小双 张光旭 陈波 蔡卫权 (Chinese journal of chemical engineering, 2013)
In the absence of catalyst, 70% hydrogen peroxide was used to oxidize succinic anhydride to solid monoperoxysuccinic acid（PSA）. Then PSA was applied to synthesis of ε-caprolactone（ε-CL） by oxidation of cyclohexanone in the heterogeneous system. In order to achieve material recycle, solid precipitated in the process of synthesizing ε-CL was dehydrated via reactive distillation followed by recrystallization to prepare succinic anhydride, which was characterized by IR（infrared spectra） and1HNMR（1H nuclear magnetic resonance）. Effects of molar ratio of PSA to cyclohexanone, acetic acid dosage, reaction temperature, reaction time on conversion of cyclohexanone, yield and selectivity of ε-CL were investigated respectively. The results indicated that conversion of cyclohexanone, yield and selectivity of ε-CL were upto 98.1%, 97.5% and 99.4% respectively under the optimal conditions. In addition, in the process of synthesizing succinic anhydride, the optimal yield of succinic anhydride reached 67.4%.